Pengawasan Pekerjaan Finishing Lantai dan Penutup Plafond (The development of Islamic University IAIN Sunan Kalijaga Project Faculty of Science and Technology Yogyakarta - Laura Christiani (Fak. Teknik Univ. Atma Jaya, 2007)
ws.c.1